2010
DOI: 10.1007/s10616-010-9280-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of phagocytic activity of macrophage-like cells by pyrogallol-type green tea polyphenols through caspase signaling pathways

Abstract: We investigated the phagocytosis-enhancing activity of green tea polyphenols, such as epigallocatechin gallate (EGCG), epigallocatechin (EGC), epicatechin gallate (ECG), epicatechin (EC) catechin (+C) and strictinin, using VD3-differentiated HL60 cells. EGCG, EGC, ECG and strictinin, but not EC and +C, increased the phagocytic activity of macrophage-like cells, and a caspase inhibitor significantly inhibited phagocytic activities. These results suggest that the pyrogallol-type structure in green tea polyphenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…An increase in the mucosal IgA secretion by dietary components is due to an enhanced antigen response caused by antigenpresenting cells (APC) and lymphocyte activation. [7][8][9] EGC has a phagocytosis-enhancing effect on macrophage-like cells via caspase activation, 10) and we confirmed that the administration of EGC for two weeks enhanced the phagocytic activity of ex vivo PP cells, but that EGCG did not (data not shown). The enhanced IgA production by EGC administration may have been due to enhancement of the antigen response by APC activation.…”
supporting
confidence: 74%
“…An increase in the mucosal IgA secretion by dietary components is due to an enhanced antigen response caused by antigenpresenting cells (APC) and lymphocyte activation. [7][8][9] EGC has a phagocytosis-enhancing effect on macrophage-like cells via caspase activation, 10) and we confirmed that the administration of EGC for two weeks enhanced the phagocytic activity of ex vivo PP cells, but that EGCG did not (data not shown). The enhanced IgA production by EGC administration may have been due to enhancement of the antigen response by APC activation.…”
supporting
confidence: 74%
“…1) enhanced the Fig. 1 Green tea catechins with a pyrogallol-type structure phagocytic activity of human macrophage-like cells (Monobe et al 2010), but could not identify the receptor involved in the activation. Recently, it was reported that at low levels, H 2 O 2 acts as a signaling molecule (Matoba et al 2000;Vanhoutte 2001).…”
Section: Resultsmentioning
confidence: 99%
“…1) enhanced the phagocytic activity of human macrophage-like cells (Monobe et al 2010). The increase in phagocytic activity was related to the activation of caspase signaling pathways (Monobe et al 2010); however, the receptor involved in the activation was not identified. Recently, a 67-kDa laminin receptor (67LR) has been identified as a cell surface receptor for gallate-type catechins (EGCG, ECG etc.)…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, curcumin and EGCG could stimulate phagocytosis of fluorescent beads by RAW murine macrophagelike cells, murine peritoneal macrophages or human HL-60 differentiated cells, with a requirement of caspases for HL-60 cells [82][83][84][85]. In vitro, curcumin and EGCG could stimulate phagocytosis of fluorescent beads by RAW murine macrophagelike cells, murine peritoneal macrophages or human HL-60 differentiated cells, with a requirement of caspases for HL-60 cells [82][83][84][85].…”
Section: Polyphenols and Macrophagesmentioning
confidence: 99%